Consensus guidelines for the diagnosis and management of invasive fungal disease due to moulds other than Aspergillus in the haematology/oncology setting, 2021. (22nd December 2021) - Bupha‐Intr, Olivia; Butters, Coen; Reynolds, Gemma; Kennedy, Karina; Meyer, Wieland; Patil, Sushrut; Bryant, Penelope; Morrissey, Catherine O.; ,
Abstract: Invasive fungal disease (IFD) due to moulds other than Aspergillus is a significant cause of mortality in patients with malignancies or post haemopoietic stem cell transplantation. The current guidelines focus on the diagnosis and management of the common non‐ Aspergillus moulds (NAM), such as Mucorales, Scedosporium species (spp.), Lomentospora prolificans and Fusarium spp. Rare but emerging NAM including Paecilomyces variotii, Purpureocillium lilacinum and Scopulariopsis spp. are also reviewed. Culture and histological examination of tissue biopsy specimens remain the mainstay of diagnosis, but molecular methods are increasingly being used. As NAM frequently disseminate, blood cultures and skin examination with biopsy of any suspicious lesions are critically important. Treatment requires a multidisciplinary approach with surgical debridement as a central component. Other management strategies include control of the underlying disease/predisposing factors, augmentation of the host response and the reduction of immunosuppression. Carefully selected antifungal therapy, guided by susceptibility testing, is critical to cure. We also outline novel antifungal agents still in clinical trial which offer substantial potential for improved outcomes in the future. Paediatric recommendations follow those of adults. Ongoing epidemiological research, improvement in diagnostics and the development of new antifungal agents will continue to improve the poor outcomes that have been traditionally associated with IFD due to NAM.